Oxidative Phosphorylation-Mediated E-Selectin Upregulation Is Associated With Endothelia–Monocyte Adhesion in Human Coronary Artery Endothelial Cells Treated With Sera From Patients With Kawasaki Disease - Zhang, Danfeng; Liu, Lingjuan; Yuan, Yuxing; Lv, Tiewei; Huang, Xupei; Tian, Jie (Frontiers in Pediatrics, 2021)
Background and aims: E-selectin is a cell-adhesion molecule of the vascular endothelium that mediates leukocyte rolling in the early inflammatory responses in many diseases including Kawasaki disease (KD). Previous studies have demonstrated that the expression levels of E-selectin was significantly increased in the sera of KD patients and in endothelial cells of KD patient’s autopsy, respectively. In this study, we aimed to examine the E-selectin levels in endothelial cells treated with sera from KD patients and explore the underlying mechanisms. Methods: Human coronary artery endothelial cells (HCAECs) were randomly incubated with sera either from healthy children (health control, HC group) or pediatric KD patients (assigned as KD with coronary artery lesion, KD-CAL+ group and KD without coronary artery lesion, KD-CAL- group). E-selectin levels were determined by RT-qPCR, Western blotting and immunofluorescence, respectively. Cell adhesion assay was performed to quantify the role of E-selectin in intercellular adhesion. High-throughput cell RNA sequencing followed by functional validation was performed to explore the underlying mechanism. Results: E-selectin levels were significantly increased in KD-CAL+ group versus HC group and KD-CAL- group. Compared with the KD-CAL- group, endothelia-monocyte adhesion was increased in the KD-CAL+ group, while E-selectin specific siRNA could significantly rescue it. High-throughput cell RNA sequencing analysis also found a significant difference in oxidative phosphorylation levels between KD-CAL+ group and KD-CAL- group. Functional validation results further confirmed that the oxidative phosphorylation was up-regulated in KD-CAL+ group and KD-CAL- group compared to HC group, while KD-CAL+ group exhibited a higher oxidative phosphorylation than KD-CAL- group. We also found that the E-selectin levels and endothelia-monocyte adhesion were significantly decreased by Oxidative phosphorylation inhibitor oligomycin in the KD-CAL+ group and KD-CAL- group, respectively. Conclusion: Sera from KD patients stimulates oxidative phosphorylation levels and enhances E-selectin expression in HCAECs, which may contribute to the development of CAL in KD patients.